Measurement of interaction between futsal footwear and futsal pitch surface under different outsole condition - Ismail, S. I.; Nunome, H.; Marzuki, F. F.; Su`aidi, I. (Proceedings, 2018)
The interaction between footwear and the pitch surface is an important aspect for successful performance and injury prevention in futsal. We aimed to investigate shoe-surface interaction of non-marking and multi-studded outsole designs. Five university players were recruited to perform two futsal specific movements (front translational traction-FTT and side translational traction-STT). A motion capture system including an embedded force plate covered by a synthetic material for futsal pitch, were utilized to collect the ground reaction force components. During FTT and STT, the multi-studded outsole was characterized by significantly higher mean peak traction forces. Moreover, although there were no significant differences in peak coefficient of traction between the two types of futsal shoes during STT, the multi-studded outsole tended to produce marginally higher peak coefficient of traction during FTT. It can be concluded that the multi-studded outsole design is prone to generate higher traction force and coefficient of traction.